Implementasi Layanan Bimbingan Kelompok Terhadap Kemampuan Adversity Quotient Siswa Sekolah Menengah Pertama - Alber Tigor Arifyanto; Dodi Priyatmo Silondae; Muhammad Akbar Abdi Darma (Psychocentrum Review, 2020)
The objective of the research was to improve the students adversity quotient competence who have been studying at the eight graders of Public Junior High School. The students improvement in their adversity quotient competence was facilitated through group guidance service. This was pre-experimental research with one group pre-test and post test design. The subjects of the research were 9 students. The result of the study showed that, Before the students have been provided with group guidance service, the students pre-test average scores were 53%.  Their competences were in low category.  After the students have been provided with group guidance service, the students post-test average scores were 70.2%. The students competences are in high category. Overall, the students adversity quotient competence is improving into 17.2%. Based on the result of inferential analyses using Wilcoxon signed rank test, it was found that it’s significant was  a = 0,05 with its Pvalue = 0.008. Pvalue ˂ a (0.008 ˂ 0.05). The test result indicates that Ha is accepted. It can therefore be concluded that group guidance service is able to improve the students’ adversity quotient competence in Public Junior High School.